Decision-making in geriatric oncology: systemic treatment considerations for older adults with colon cancer. (1st December 2016) - Moth, Erin B.; Vardy, Janette; Blinman, Prunella
ABSTRACT: Introduction : Colon cancer is common and can be considered a disease of older adults with more than half of cases diagnosed in patients aged over 70 years. Decision-making about treatment with chemotherapy for older adults may be complicated by age-related physiological changes, impaired functional status, limited social supports, concerns regarding the occurrence of and ability to tolerate treatment toxicity, and the presence of comorbidities. This is compounded by a lack of high quality evidence guiding cancer treatment decisions for older adults. Areas covered : This narrative review evaluates the evidence for adjuvant and palliative systemic therapy in older adults with colon cancer. The value of an adequate assessment prior to making a treatment decision is addressed, with emphasis on the geriatric assessment. Guidance in making a treatment decision is provided. Expert commentary : Treatment decisions should consider goals of care, a patient's treatment preferences, and weigh up relative benefits and harms.